Genetic Characteristics and Variation Spectrum of USH2A-Related Retinitis Pigmentosa and Usher Syndrome - Li, Wei; Jiang, Xiao-Sen; Han, Dong-Ming; Gao, Jia-Yu; Yang, Zheng-Tao; Jiang, Li; Zhang, Qian; Zhang, Sheng-Hai; Gao, Ya; Wu, Ji-Hong; Li, Jian-Kang (Frontiers in Genetics, 2022)
ABSTRACT Purposes: We aimed to characterize the USH2A genotypic spectrum in Chinese cohort, and providing detailed genetic profile for Chinese patients with USH2A-IRD. Methods: Retrospective study. A total of 1,334 patients diagnosed with IRD were recruited as study cohort, including 1,278 RP and 56 USH patients, as well as other types of IEDs patients and healthy family members (n = 7,376) as controls cohort. The genotype-phenotype correlation of all participants with USH2A variant was evaluated. Results: Etiological mutations in USH2A, the most common cause of RP and USH, were found in 218 (16.34%, 218/1,334) genetically solved IRD patients, with prevalences of 14.87% (190/1,278) and 50% ( 28/56). After bioinformatics and QC processing, 768 distinct USH2A variants were detected in total of 8,710 participants, including 136 disease-causing mutations present in 665 alleles, distributed within 5.81% (506/8,710) participants. Of these 136 mutations, 43 were novel, as well as 9 founder mutations and 2 hot spot mutations with allele count ≥ 10. Furthermore, 38.5% (84/218) of genetically solved USH2A-IRD patients were caused by at least one of both c.2802T>G and c.8559-2A>G mutations, and 36.9% and 69.6% of the alleles in the RP and USH groups were truncating, respectively. Conclusions: USH2A-related East Asian-specific founder and hot spot mutations were the major causes for Chinese RP and USH patients. Our study systematically delineated the genotype spectrum of USH2A-IRD, enable accurate genetic diagnosis, and provide East Asian and other ethnicities with baseline data of Chinese origin, which would better serve genetic counseling and therapeutic targets selection.